PENGARUH JARAK NOSEL UDARA DENGAN OUTLET TERHADAP DIS-TRIBUSI UKURAN BUBBLE YANG DIHASILKAN OLEH MBG TIPE SWIRL - Drajat Indah Mawarni; Indarto Indarto; Deendarlianto Deendarlianto; Wiratni Budhijanto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
This research uses a swirl type MBG (MBG) with the gap variation between the air nozzle and the outlet of 1, 5 and10 mm. In this experiment, we used a tangential inlet of 25 mm and an outlet of 20 mm with a water flow rate of 20 – 70 l/min and an air flow rate range of 0.1 – 0.8 l/min, to determine the characteristics of MBG which include bubble distribution, pressure drop, hydraulic power, and efficiency. The probability of the diameter of the microbubble formed was in the range of 90 – 150 µm for all variations of the air nozzle gap. The larger the incoming water flow rate, the smaller the diameter of the bubbles formed, whereas if the water flow rate decreases, the diameter of the bubbles formed will increase. In contrast to the water flow rate, if the air flow rate increases, the diameter of the bubbles formed will increase, whereas if it decreases, the diameter of the bubbles will decrease. From the signal processing data, information was obtained about the comparison of the pressure drop of the three variations of the air nozzle gap, as follows: The higher the water flow rate, the pressure drop and hydraulic values increase significantly, while for air flow rate, the higher the air flow rate, the pressure drop and hydraulic power values will increase albeit not significantly. As for MBG efficiency, it will decrease significantly with increasing water flow rate and will increase insignificantly with decreasing water flow rate.